HOUSEHOLD PREPAREDNESS FOR FLOOD DISASTER IN SURAKARTA CITY 2017 - ika rahmawati; Chatarina Muryani; Setya Nugraha (Universitas Sebelas Maret (UNS), 2018)
This research case aims to determine (1) The spread of floods in the city of Surakarta in 2016; (2) Uncertainty factors that causing floods based on community perception in Surakarta City; (3) Individual and household preparedness levels in dealing with flood disaster in Surakarta City; (4) Implementation of science as a teaching material of geography in grade XI Senior High School on basic material of natural disaster mitigation.The research was conducted in Western City of Surakarta. The area assumed in Western City of Surakarta are Banjarsari district, Laweyan District, and Serengan District. Eligible samples consisted of 11 villages affected by flood in 2016, sampling of administrative unit using purposive sampling technique. The sample has been taken is the number of individuals / households in each ‘RW’ affected by floods in each villages, the number of samples is using snowball sampling technique. Data collection was done by documentation study, interview, questionnaire, and interview. Data validity test is done by data triangulation method. Data analysis is using Likert approach and LIPI preparedness measurement framework - UNESCO / ISDR.The results of the research are as follows: (1) flooding spread in eleven sub-districts in West Surakarta City which is divided into 3 regions based on administrative unit of analysis. Banjarsari District having local flood characteristics and submissions with elevation and duration of time falling into the low category. Laweyan District areas have local flood characteristics and postings with elevation and duration of time that falling into the low category. Serengan District has local flood characteristics and post with elevation and duration falling into the medium category; (2). Factors causing high flooding, garbage disposal, and flood control building conditions; (3) Individual and household preparedness studies in all villages are in a ready category;